Correlation between non-robosomal peptide synthetase (NRPS) production and virulence of Ganoderma boninense PER71 on oil palm (Elaeis guineensis) - Chua, Jackie; Kwan, Yee Min; Othman, Abrizah; Wong, Mui Yun (Malaysian Palm Oil Board, 2021)
Basal stem rot (BSR) disease caused by the white rot fungus Ganoderma boninense is the most destructive oil palm disease leading to production losses in fresh fruit bunches. Non-ribosomal peptide synthetase (NRPS) plays an important role in fungal pathogenicity. These large multi-modular enzymes catalyse the biosynthesis of secondary metabolites that act as fungal virulence factors. In this study, the detection of NRPS in G. boninense was achieved using polymerase chain reaction (PCR)-based method. Core motifs of adenylation domain of NRPS gene was identified in G. boninense. The deduced amino acid sequence showed similarity to the conserved core motifs (A2, A3 and A5) of the adenylation domain. Siderophores were predicted as the potential secondary metabolites synthesised by NRPS. Expression analysis of GbNRPS in 3-month-old oil palm artificially infected with G. boninense has confirmed the upregulation of GbNRPS at 1 month after inoculation (MAI) peaking at 4 MAI in susceptible clone but not in tolerant clone. There was a correlation between GbNRPS gene expression and disease severity. Susceptible clones showed significantly higher disease severity index (DSI) (62.50%) compared to tolerant clones (28.13%) at 4 MAI. This is the first putative detection of adenylation domain of NRPS (GbNRPS) gene and functional analysis of NRPS as a virulence factor in disease development.